Auctions and leaks: A theoretical and experimental investigation - Sven Fischer; Werner Güth; Todd R. Kaplan; Ro'i Zultan (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We study first- and second-price private value auctions with sequential bidding where second movers may discover the first movers bids. There is a unique equilibrium in the first-price auction and multiple equilibria in the second-price auction. Consequently, comparative statics across price rules are equivocal. We experimentally find that in the first-price auction, leaks benefit second movers but harm first movers and sellers. Low to medium probabilities of leak eliminate the usual revenue dominance of first-price over second-price auctions. With a high probability of a leak, second-price auctions generate higher revenue.
Keywords: C72; C91; D44; 330; auctions; collusion; espionage; laboratory experiments